Perancangan Instrumen Kematangan Integrasi Sistem Manufaktur (Studi Kasus Perusahaan Flow Line Production) - Yudha Prasetyawan; Novita Anggraini Wibowo; Siti Cholifah (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2013)
The purpose of this research is to design maturity instrument for manufacturing systems integration usingself assessment questionnaire. The model design has 10 criteria based on six key performance indicators and15 combined indicators from CIM Wheel and Critical Success Factor Framework of CIM. Indicators havedesigned by reasoning process in component model combination. The model was applied into PT CharoenPokphand Poultry Feed Krian and PT. Petrokimia Gresik Plant I.Results of this assessment showed that PT Charoen Pokphand Krian was at VI maturity level with 86.15%showing the highest achievement of Key Performance Indicator (KPI) criteria, whole information wasdeployed, improvement and innovation as a primary key, effective integration and automation has almostreached the enterprise level. PT. Petrokimia Gresik was at V maturity level with 79.03% which shows agood achievement for the KPI criteria, well information deployed, improvement has been made, integrationand automation in plant level.